(untitled) (American Journal of Management, 2023)
Successful implementation of lean six sigma (LSS) program requires both organizational and workforce competencies. This paper hypothesizes that workforce skills and competencies needed to execute LSS develops through experience with other data driven quality systems and lean implementations, and the foundation for a quality culture for Lean six-sigma (LSS) takes root only through years of practice. Although literature demonstrates the requirements for a dominant quality culture for LSS, the competency issues have not been addressed through a formal study. In this study we address the workforce competency issues through detailed analyses of eight LSS implementations. These selected LSS companies were categorized, through a detailed study, into successful and unsuccessful adopters based on their level of experience with quality programs. Seven workforce competency variables – the content validity of which were verified through literature review – were tested for both successful and unsuccessful adopters support our hypothesis that competency for LSS develops through implementation of other quality/lean programs that are precursors to LSS. Most unsuccessful LSS adopters performed poorly on all workforce competency dimensions, but their performance on goal setting and process control & improvement were the poorest.